Nanosecond repetitively pulsed discharges in N2–O2 mixtures: inception cloud and streamer emergence. (27th March 2015) - Chen, She; Heijmans, L C J; Zeng, Rong; Nijdam, S; Ebert, U
Abstract: We evaluate the nanosecond temporal evolution of tens of thousands of positive discharges in a 16 cm point-plane gap in high purity nitrogen 6.0 and in N2 –O2 gas mixtures with oxygen contents of 100 ppm, 0.2%, 2% and 20%, for pressures between 66.7 and 200 mbar. The voltage pulses have amplitudes of 20 to 40 kV with rise times of 20 or 60 ns and repetition frequencies of 0.1 to 10 Hz. The discharges first rapidly form a growing cloud around the tip, then they expand much more slowly like a shell and finally after a stagnation stage they can break up into rapid streamers. The radius of cloud and shell in artificial air is about 10% below the theoretically predicted value and scales with pressure p as theoretically expected, while the observed scaling of time scales with p raises questions. We find characteristic dependences on the oxygen content. No cloud and shell stage can be seen in nitrogen 6.0, and streamers emerge immediately. The radius of cloud and shell increases with oxygen concentration. On the other hand, the stagnation time after the shell phase is maximal for the intermediate oxygen concentration of 0.1% and the number of streamers formed is minimal; here the cloud and shell phase seem to be particularly stable against destabilization into streamers.